1994
DOI: 10.1164/ajrccm.149.3.7509703
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of cell loss during bronchoalveolar lavage fluid processing. Effects of fixation and staining methods.

Abstract: Discrepancies have been reported in differential cell counts according to the diverse processing methods used in bronchoalveolar lavage (BAL) fluid management. The differences have proved to be mainly the result of selective lymphocyte loss, while the exact mechanisms of the phenomenon remain controversial. Observing a similar variation in differentials from differently stained identical smears, we quantified the cell loss due to staining procedures from 45 consecutive satisfactory BAL procedures. To do this, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 0 publications
1
10
0
Order By: Relevance
“…The most representative age group was up to 5 years. 71% of the patients with lung infiltrates in our study were below the age of 5, as other authors have reported (9,10). In our study, the presentation of CD4+and CD8+ lymphocytes in BAL in the studied group shows a small percentage of CD8+ lymphocytes as an immune response in 8-10% of patients, while the cellular response of CD4 +lymphocytes in the sample itself was present up to 14% in the entire group of the diseased children.…”
Section: Discussionsupporting
confidence: 71%
“…The most representative age group was up to 5 years. 71% of the patients with lung infiltrates in our study were below the age of 5, as other authors have reported (9,10). In our study, the presentation of CD4+and CD8+ lymphocytes in BAL in the studied group shows a small percentage of CD8+ lymphocytes as an immune response in 8-10% of patients, while the cellular response of CD4 +lymphocytes in the sample itself was present up to 14% in the entire group of the diseased children.…”
Section: Discussionsupporting
confidence: 71%
“…To date, the effects of on‐slide fixation on BALF samples have only been determined concerning lymphocyte loss and identification of mast cells in human BALF and included a wet‐spray fixation method, and formaldehyde and methanol fixation methods . In equine clinical diagnostics, fixatives such as a formalin saline solution and Saccamanno fixative (an alcohol‐based solution) have been used exclusively as prefixatives added to BALF prior to slide preparation but on‐slide fixation methods on the prepared slide as performed in the present study have not been published.…”
Section: Discussionmentioning
confidence: 99%
“…BAMBI, BMP and activin membrane-bound inhibitor. (Xaubet et al 1991;Moumouni et al 1994), there is still no notable method for long-term storage of BAL. Therefore, this study presents a novel and simple method for fixation of BAL cells that allows a plethora of applications besides long-term storage.…”
Section: Discussionmentioning
confidence: 99%